Screening for Opioid Use Disorder in the Largest Jail in Arkansas: A Brief Report. (July 2019) - Zaller, Nickolas; Donadeo, Kristin; Coffey, James; Zielinski, Melissa; Brinkley-Rubinstein, Lauren
Individuals who have experienced incarceration have an increased risk of both fatal and nonfatal overdose. Given the increases in illicit opioid use in Arkansas and across the South, many individuals with opioid use disorder (OUD) are likely to encounter the criminal justice system, particularly county jails. However, there are currently no published data on OUD among entrants into county jails in the South. This study presents data from an OUD screening project initiated by the Pulaski County Regional Detention Facility, the largest county jail in the state of Arkansas. As part of the regular intake process, a jail staff person administered the Rapid Opioid Dependence Screen. De-identified data were provided to researchers at the University of Arkansas for Medical Sciences. The data clearly show an increased prevalence of OUD, justifying the need for evidence-based substance use programs such as MAT in jail settings in the South.